Immune Checkpoint Blockade Therapy for Hepatocellular Carcinoma: Clinical Challenges and Considerations - Zhang, Qi; Chen, Yiwen; Bai, Xueli; Liang, Tingbo (Frontiers in Oncology, 2020)
Although many approaches have been developed to treat hepatocellular carcinoma (HCC), which displays high incidence and mortality, especially in Asian countries, the prognosis of patients with HCC remains dismal. Immunotherapy, particularly immune checkpoint inhibitors show encouraging efficacy and have been widely applied in the clinic. However, in contrast to traditional therapies, immunotherapy brings many challenges when used in a real world, including biomarker discovery, response evaluation, and adverse event treatment. In this review, we introduce some important and intractable issues in current clinical practice regarding the strategy of immune checkpoint blockade, review the current evidence, and discuss the critical challenges and possible future approaches.